2014
DOI: 10.1039/c4tc00791c
|View full text |Cite
|
Sign up to set email alerts
|

Oil-in-water microemulsion: an effective medium for triplet–triplet annihilated upconversion with efficient triplet acceptors

Abstract: An upconverted oil-in-water microemulsion containing a bimolecular system was first reported for the triplet–triplet annihilated upconversion by temperature effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The need to extend this phenomenon to water environment and to biological specimen triggered remarkable efforts in the preparation of TTA‐UC structures. Among them, active polymeric structures, ionogels, liposomes, different supramolecular approaches, oil in water microemulsions, dendrimers, micelles, and water dispersible nanoparticles and nanocapsules led to demonstration of the applicability of TTA‐UC both in vitro and in vivo, within the tissue transparency window …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to extend this phenomenon to water environment and to biological specimen triggered remarkable efforts in the preparation of TTA‐UC structures. Among them, active polymeric structures, ionogels, liposomes, different supramolecular approaches, oil in water microemulsions, dendrimers, micelles, and water dispersible nanoparticles and nanocapsules led to demonstration of the applicability of TTA‐UC both in vitro and in vivo, within the tissue transparency window …”
Section: Introductionmentioning
confidence: 99%
“…The approach is general and versatile, yet somewhat complicated by its multistep nature. Oil in water microemulsions, requiring an organic solvent based inner phase, also offer a viable and general way to prepare colloids displaying efficient TTA‐UC in oxygenated environment . Very recently Yanai and co‐workers demonstrated that the synthesis and water phase self‐assembly of amphiphilic cationic acceptor molecules with anionic donor (sensitizer) molecules provides an efficient way to address the oxygen quenching issue by a purely supramolecular approach .…”
Section: Introductionmentioning
confidence: 99%
“…Triplet‐triplet annihilation (TTA) with multi‐chromophores system comprising a triplet sensitizer and an acceptor is an effective approach to generating upconverted fluorescence using low‐power laser (<100 mW/cm 2 , equal to the sunlight), which was firstly demonstrated by Parker and Hatchard in 1962 and has significant applications so far, such as photovoltaics, photocatalysis and bioimaging . According to the revealed mechanism, TTA‐upconversion undergoes a series of multiple quantum processes: (i) the sensitizer first absorbs one photon to the excited singlet state and goes across its triplet excited state by intersystem crossing (ISC); (ii) then, the triplet–triplet energy transfer (TTET) occurs from the sensitizer to the acceptor, and then two triplet acceptors undergo the triplet‐triplet annihilation (TTA) with the result that photon‐upconversion is produced.…”
Section: Main Textmentioning
confidence: 99%
“…One can find, however, various modifications of SDME that more or less differ from the above‐described general procedure. Examples of the application the two most commonly used modes of SDME—HS and DI—can be found in the Supporting Information …”
Section: General Procedures Of Single‐drop Microextraction (Sdme)mentioning
confidence: 99%